Enduring Uncertainty: Deportation, Punishment and Everyday Life - Hasselberg, Ines (Enduring Uncertainty, Deportation, Punishment and Everyday Life, 2016)
This volume provides fascinating insights into the deportation process as it is felt and understood by those subjected to it. The author presents a rich and innovative ethnography of deportation and deportability experienced by migrants convicted of criminal offenses in England and Wales. This title was made Open Access by libraries from around the world through Knowledge Unlatched.
Includes bibliographical references and indexes.
The politics of deportation -- Living the law -- Surveillance and control -- Undecided present, uncertain futures -- On compliance and resistance.
This volume provides fascinating insights into the deportation process as it is felt and understood by those subjected to it. The author presents a rich and innovative ethnography of deportation and deportability experienced by migrants convicted of criminal offenses in England and Wales. This title was made Open Access by libraries from around the world through Knowledge Unlatched.
Focusing on the lived experience of immigration policy and processes, this volume provides fascinating insights into the deportation process as it is felt and understood by those subjected to it. The author presents a rich and innovative ethnography of deportation and deportability experienced by migrants convicted of criminal offenses in England and Wales. The unique perspectives developed here – on due process in immigration appeals, migrant surveillance and control, social relations and sense of self, and compliance and resistance – are important for broader understandings of border control policy and human rights.
Also issued in print and PDF version.
Keywords: Refugee & Migration Studies.; Politics.